ANALISIS HASIL BELAJAR FISIKA SISWA MENGGUNAKAN ONGOING ASSESSMENT TEKNIK IF-AT - Risdianto Parhat; Undang Rosidin; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
Assessment plays a very important role in improving student’s physics learning result. However, the less variety of assessment used by the teacher causes the low score of student’s physics learning result. One type of assessment used in the research that can increase student’s physics learning result is Ongoing Assessment IF-AT (Immediate Feedback Assessment Technique). This kind of as-sessment is not only applied when the learning is over, but also done continuously when the learning process happens, that are: at the beginning of learning, whilst learning, and at the end of the learning process. This research also supported by Problem Based Learning (PBL) model. Objective of this research are to know the influence score of Ongoing Assessment IF-AT technique toward score of student’s physics learning result through PBL model. The data score of Ongoing Assessment IF-AT technique is obtained from the average score of multiple-choice test of IF-AT technique conducted from 3 meetings, while the data score of learning result is obtained from cross-technique multiple-choice test conducted in the last meet-ing. Research results show that there is a positive linear influence score of Ongo-ing Assessment IF-AT technique toward score of student’s physics learning result through PBL model.Keywords : Score of learning result, score of ongoing assessment IF-AT technique,Problem Based Learning (PBL) model.